Я познаю мир : страны и народы: Европа: Дет. энцикл. / Авт. -сост. Л. А. Багрова; Худож. Е. В. Гальдяева, А. В. Кардашук - Багрова Людмила Алексеевна (АСТ, 2001)
Экземпляры: (20170203) / Инвентарный номер: 28298 / Цена: / Сис.шифр: 26.8 / Авт.знак: Я 11 / ББК: 26.89(4)я2